Management of Learning Environment in Studio Class at Seraphim Music Studio - Mahendra, Marda Putra (Universitas Negeri Surabaya, 2023)
Seraphim Music Studio is a professional non-formal music school specializing in arts education, particularly music education. Undoubtedly, Seraphim Music Studio boasts internationally certified and professional instructors in their respective fields. The cornerstone of effective learning lies in adequate classroom spaces. The management of a conducive learning environment significantly influences the learning process in the classroom. As one of the non-formal music schools in Surabaya, Seraphim Music Studio has designed all its classrooms as studio spaces. Several challenges arise in the development of these studio classrooms, including spatial limitations, diversity in musical instruments, and studio class management. This research employs a qualitative research method, focusing on data collection through interviews, observations, and document analysis to understand complex and contextual phenomena. The findings of this article reveal that Seraphim Music Studio identifies 7 standards for studio classroom facilities and service management that must be met. These standards include service speed, information accuracy, and courtesy in communication. Keywords for this abstract include Seraphim Music Studio, non-formal music education, internationally certified instructors, studio classrooms, learning environment management, and service standards.